PENGARUH PENGGUNAAN MEDIA CD INTERAKTIF TERHADAP PEMAHAMAN KONSEP SOSIOLOGI SISWA KELAS XI IPS DI MAN 3 PADANG - ayu, Helvi mesra (Pendidikan Sosiologi, 2014)
Low students understanding of concepts in sociology during this 3 ManPadang , shows the need for improvements to the system that teachers learning .In keeping with the times and aspects of the present moment , the technology toachieve learning goals , researchers interested in examining the effect of the use ofInteractive CD media . This study aims to look at the effect of the use of theInteractive CD media sociology student understanding of concepts .The experimental studies conducted in the second half in Padang Man 32013/2014 school year . The study population is all students of class XI Ipsconsisting of 2 classes , and sampling techniques that total sampling because thereare only 2 classes . Class XI Ips 1 as the control class in learning lecture method ,class XI and class Ips 2 as a learning experiment using Interactive CD media .Data were collected by providing objective test to both groups . To test thehypothesis using t-test .Based on the hypothesis the obtained results tcount > ttable or 3.2668 > 1.645 .at significant level 0.05, then H0 is rejected and H1 as they arrive means usingInteractive CD media sociology student understanding of the concept ofincreasing both overall and material concept . This is because in the process oflearning the interaction between stimulus and response , in which the stimulus isInteractive CD media by teachers , and students respond with changes thatstudents watch , observe , and listen to learning material through the InteractiveCD media , so that students in the learning process mentally engaged . Based onthe above results it can be concluded that the Interactive CD media can enhancestudents understanding of the concept of sociology .